Etiology and outcome of intestinal obstruction: an institutional prospective study - Maniselvi, S.; Gayathre, S. P. (International Surgery Journal, 2018)
Background: Intestinal obstruction is a major part of the emergency caseload in a general surgical department. It can pose diagnostic and treatment challenges with its varied presentation and multiple management options. The surgeon needs to use astute judgment to spot the diagnosis and plan the line of management. The aim of the study is to show the various etiologies most commonly presenting with intestinal obstruction in our institute in north Chennai. It also aims to evaluate markers of postoperative morbidity. Methods: This is a prospective study of about 50 patients with acute intestinal obstruction coming to the emergency department of the Government Stanley Medical College and Hospital from the time the patients were admitted they were followed up till their time of discharge/ death. X-ray abdomen erect and supine and CECT abdomen and pelvis were routinely taken for all the patients. Results: X-ray abdomen supine showed multiple air fluid levels as the commonest finding which was seen in 42 cases, 27 cases had dilated bowel loops and 2 cases showed coffee bean appearance. 6 cases had fluid levels less than 3 and were deemed in 49 cases and was inconclusive in 1 case to be inconclusive. CECT showed features of obstruction or pathological obstruction point. Conclusions: Corrections of dehydration and rapid resuscitation with correction of electrolyte disturbances would go a long way in reducing morbidity and mortality. Surgical intervention in a timely manner is the treatment of choice and prognosis is good when it is not delayed.